2001
DOI: 10.1016/s0022-5347(05)65855-7
|View full text |Cite|
|
Sign up to set email alerts
|

High Dose Radiation Delivered by Intensity Modulated Conformal Radiotherapy Improves the Outcome of Localized Prostate Cancer

Abstract: Sophisticated conformal radiotherapy techniques with high dose 3-D conformal and intensity modulated radiation therapy improve the biochemical outcome in patients with favorable, intermediate and unfavorable risk prostate cancer. Intensity modulated radiation therapy is associated with minimal rectal and bladder toxicity, and, hence, represents the treatment delivery approach with the most favorable risk-to-benefit ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
143
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 613 publications
(151 citation statements)
references
References 30 publications
3
143
0
5
Order By: Relevance
“…Because of higher doses, margins needed to compensate prostate motion [2,14] and other treatment uncertainties, there is an increased risk of dose limiting side effects [9,32] or underdosing the target. To minimize toxicity while delivering high doses to the target, a possible solution would be to localize the prostate position daily before treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Because of higher doses, margins needed to compensate prostate motion [2,14] and other treatment uncertainties, there is an increased risk of dose limiting side effects [9,32] or underdosing the target. To minimize toxicity while delivering high doses to the target, a possible solution would be to localize the prostate position daily before treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In primary treatment of localized prostate cancer with external-beam radiotherapy, the advantage of dose escalation has been demonstrated in retrospective [15,21,29] and prospective [22] studies. Late rectal toxicity, in particular late rectal bleeding, is considered the limiting factor [17,24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent study demonstrated that increased use of lung IMRT reduced the likelihood of hospitalization for dehydration or pulmonary toxicity [19]. Improving normal tissue dose distributions beyond three-dimensional conformal radiotherapy clearly contributes to reduced morbidity for breast, prostate cancer and head and neck cancer patients [4,[20][21]. IMRT is clearly justified when advanced technology enables dose escalation thereby improving locoregional tumor control [22].…”
Section: Discussionmentioning
confidence: 99%